Autophagy and leucine promote chronological longevity and respiration proficiency during calorie restriction in yeast - Aris, John P. (2013)
We have previously shown that autophagy is required for chronological longevity in the budding yeast Saccharomyces cerevisiae. Here we examine the requirements for autophagy during extension of chronological life span (CLS) by calorie restriction (CR). We find that autophagy is upregulated by two CR interventions that extend CLS: water wash CR and low glucose CR. Autophagy is required for full extension of CLS during water wash CR under all growth conditions tested. In contrast, autophagy was not uniformly required for full extension of CLS during low glucose CR, depending on the atg allele and strain genetic background. Leucine status influenced CLS during CR. Eliminating the leucine requirement in yeast strains or adding supplemental leucine to growth media extended CLS during CR. In addition, we observed that both water wash and low glucose CR promote mitochondrial respiration proficiency during aging of autophagy-deficient yeast. In general, the extension of CLS by water wash or low glucose CR was inversely related to respiration deficiency in autophagy-deficient cells. Also, autophagy is required for full extension of CLS under non-CR conditions in buffered media, suggesting that extension of CLS during CR is not solely due to reduced medium acidity. Thus, our findings show that autophagy is: (1) induced by CR, (2) required for full extension of CLS by CR in most cases (depending on atg allele, strain, and leucine availability) and, (3) promotes mitochondrial respiration proficiency during aging under CR conditions.